MERDEKA BELAJAR BAGI ANAK USIA DINI BERKEBUTUHAN KHUSUS (Penelitian Studi Kasus Pelaksanaan Kebijakan Merdeka Belajar dalam Lingkup Pendidikan Luar Biasa Bagi Anak Usia Dini Berkebutuhan Khusus di Sekolah Khusus Negeri 02 Serang) - Farah Firdiarahma, - (2021)
This study aims to examine the steps, direct or short-term impacts and obstacles or obstacles and the carrying capacity of the implementation of the Merdeka Belajar policy for early childhood with special needs. This research uses a qualitative approach with a case study method. The research was conducted at SKH Negeri 02 Serang City with research subjects including administrators, two teachers of TKLB Negeri 02 Serang City, students and two parents of students. Data were collected by using observation, interview and documentation study methods. The main instrument is the researcher himself assisted by the guidelines for observation, interviews and documentation studies. The data obtained were analyzed using the Miles and Huberman interactive model.The results showed that among the steps in implementing the Merdeka Belajar policy at SKH were conducting PPDB not using a zoning system but capacity, the preparation of the RPPH took into account certain points and principles with the RPPH format consisting of three core points, namely learning objectives, learning activities or processes and assessment. . Assessment in early childhood is carried out at the beginning of the acceptance of new students. Among the carrying capacity and obstacles to the implementation of the Merdeka Belajar policy are the provision of internet quotas and activity ideas provided by the Ministry of Education and Culture for students and educators as well as adequate infrastructure facilities, while the existing obstacles are parents who cannot be invited to cooperate in learning activities and the specificity of each child . There is a direct impact in the implementation of the Merdeka Belajar policy on institutions, educators and other parties (parents and students).